New multivariate linear regression real and reactive branch flow models for volatile scenarios - Appalasamy S.; Jones O.D.; Moin N.H.; Sin T.C. (IEEE Computer Society, 2023)
Electric load flow; Least squares approximations; Regression analysis; Branch flow; flexible; Multivariate linear regressions; Power flow equations; Power systems operation; Prediction accuracy; robust; Underlying factors; Linear regression